Brain activity during transient sadness and happiness in healthy women. - George, Mark S.; Ketter, Terence A.; Parekh, Priti I. (American Journal of Psychiatry, 1995)
Objective: The specific brain regions involved in the normal emotional states of transient sadness or happiness are poorly understood. The authors therefore sought to determine if H215O positron emission tomography (PET) might demonstrate changes in regional cerebral blood flow (rCBF) associated with transient sadness or happiness in healthy adult women. Method: Eleven healthy and never mentally ill adult women were scanned, by using PET and H215O, during happy, sad, and neutral states induced by recalling affect-appropriate life events and looking at happy, sad, or neutral human faces. Results: Compared to the neutral condition, transient sadness significantly activated bilateral limbic and paralimbic structures (cingulate, medial prefrontal, and mesial temporal cortex), as well as brainstem, thalamus, and caudate/putamen. In contrast, transient happiness had no areas of significantly increased activity but was associated with significant and widespread reductions in cortical rCBF, especially in the right prefrontal and bilateral temporal-parietal regions. Conclusions: Transient sadness and happiness in healthy volunteer women are accompanied by significant changes in regional brain activity in the limbic system, as well as other brain regions. Transient sadness and happiness affect different brain regions in divergent directions and are not merely opposite activity in identical brain regions. These findings have implications for understanding the neural substrates of both normal and pathological emotion. Reprinted by permission of the publisher.